Assessment of the energy consumption and technologies in the bakery and pastry sector - Morais, Diogo (2019)
Nowadays, all industry, including the agri-food sector, faces the urgent need to increase its competitiveness in order to survive in a global market. In this context, it is vital to ensure a strong, renewed and innovative industrial base throughout all stages of the value chain, capable of competing internationally and differentiating itself by the quality of its products and services. Since wealth generation cannot be dissociated from productivity, which in turn is closely related to the trinomial: processes, technologies and quality, it is concluded that the implementation of this strategy requires a commitment to the qualification of organizational management, operational management, project management and processes and productive systems themselves and associated technologies. This paper presents the characterization of the energy consumption and technologies in bakery and pastry sector, one of the most significant in the Portuguese agri-food sector, by the analysis of the existing knowledge and information as well as from audits conducted in 17 companies distributed along North, Center and Alentejo regions. The results of this characterization aim to support the guidelines for training the SMEs of this sector in energy efficiency and for the adoption of new technologies in the production process based on Information and Communication Technologies & Electronics (ICTE).